O "Kronosie" Gombrowicza. Z profesorem Jerzym Jarzębskim rozmawia Krystyna Pietrych - Pietrych, Krystyna; Jarzębski, Jerzy (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2013)
Professor Krystyna Pietrych interviews Professor Jerzy Jarzębski, expert on the works of Witold Gombrowicz, editor of Kronos – a secret diary of the writer, hitherto unknown to the public. Jarzębski talks about the difficulties he encountered while working on the text, as well as new aspects of personality and biography of the artist unearthed by the diary.